The Influence of Raw Material Costs and Direct Labor Costs on Production Cost Efficiency (Case Study at the Sumedang Asoy Tofu Factory for the period 2018-2021) - Maria Ulfa; Suci Putri Lestari; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine and analyze the effect of the variable costs of raw materials and direct labor costs on the efficiency of production costs at the Sumedang Asoy Tofu Factory. The research method used is a case study. The data used are primary data and secondary data. These are raw material cost data, direct labor cost data, and production cost data for the 2018-2021 period. Based on the results of the study, it is known that the cost of raw materials and direct labor costs simultaneously have a significant effect on production costs. The cost of raw materials partially has a significant effect on the efficiency of production costs. Partial labor costs have a significant effect on the efficiency of production costs. Therefore, the Sumedang Asoy Tofu Factory must spend on raw material costs and direct labor costs efficiently and effectively in order to reduce production costs.